2021
DOI: 10.1007/s00011-021-01446-1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 illness and autoimmune diseases: recent insights

Abstract: Background The aim of this review is to explore whether patients with autoimmune diseases (AIDs) were at high risk of infection during the COVID-19 epidemic and how severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic affected immune system. Methods A systematic literature search was performed using the foreign databases (NCBI, web of science, EBSCO, ELSEVIER ScienceDirect) and Chinese databases (WanFang, CNKI (China National Knowledge Infrastructure), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 199 publications
1
22
0
2
Order By: Relevance
“…During COVID-19, it has been shown that ACE2-expressing macrophages contained SARS-CoV-2 nucleoprotein antigen. These cells also showed an upregulation of IL-6, which may contribute to the excessive inflammatory burden and correlate with the disease severity [23]. Moreover, other proinflammatory chemokines and pro-inflammatory cytokines may be secreted by SARS-CoV-2-infected alveolar macrophages, which may further enhance the inflammation [23].…”
Section: Sars-cov-2 Infection and Immune Responsementioning
confidence: 97%
See 2 more Smart Citations
“…During COVID-19, it has been shown that ACE2-expressing macrophages contained SARS-CoV-2 nucleoprotein antigen. These cells also showed an upregulation of IL-6, which may contribute to the excessive inflammatory burden and correlate with the disease severity [23]. Moreover, other proinflammatory chemokines and pro-inflammatory cytokines may be secreted by SARS-CoV-2-infected alveolar macrophages, which may further enhance the inflammation [23].…”
Section: Sars-cov-2 Infection and Immune Responsementioning
confidence: 97%
“…These cells also showed an upregulation of IL-6, which may contribute to the excessive inflammatory burden and correlate with the disease severity [23]. Moreover, other proinflammatory chemokines and pro-inflammatory cytokines may be secreted by SARS-CoV-2-infected alveolar macrophages, which may further enhance the inflammation [23]. Interestingly, during COVD-19, two chemokines (CCL2 and CCL7) resulted to be increased in the bronchoalveolar fluid [24].…”
Section: Sars-cov-2 Infection and Immune Responsementioning
confidence: 98%
See 1 more Smart Citation
“…According to recent publication, patients diagnosed with systemic autoimmune diseases do not seem to carry an increased risk of COVID‐19 as compared to the general population (Emmi et al, 2020 ). Moreover, even if it has been speculated that SARS‐COV‐2 infection could activate lymphocytes and inflammatory response, preliminary studies suggested that the risk of developing severe forms of COVID‐19 in patients with AD, treated with immunomodulators or biologics, might not increase (Li et al, 2021 ).…”
Section: Tablementioning
confidence: 99%
“…Таким образом, иммунная система организма человека в борьбе с коронавирусом SARS-CoV-2 подвергается выраженным колебаниям и дисфункции в виде иммуносупрессии и активации явления аутоиммунитета [ 45,53,54].…”
Section: Reviewunclassified